17β‐estradiol rescues damages following traumatic brain injury from molecule to behavior in mice. Issue 2 (23rd August 2017) - Lu, Huaihai; Ma, Kun; Jin, Liwei; Zhu, He; Cao, Ruiqi
Abstract : Traumatic brain injury (TBI) is a public health concern, and causes cognitive dysfunction, emotional disorders, and neurodegeration, as well. The currently available treatments are all symptom‐oriented with unsatifying efficacy. It is highly demanded to understand its underlying mechanisms. Controlled cortical impact (CCI) was used to induce TBI in aged female mice subjected to ovariectomy. Brain damages were assessed with neurological severity score, brain infarction and edema. Morris water maze and elevated plus maze were applied to evaluate the levels of anxiety. Apoptosis in the hippocampus was assayed with Fluoro‐Jade B staining and TUNEL staining. Western blot was employed to measure the expression of NMDA receptor subunits and phosphorylation of ERK1/2, and biochemical assays were used to estimate oxidative stress. 17beta‐Estradiol (E2) was intraperitoneally administered at 10–80 μg/kg once per day for 7 consecutive days before or after CCI. Chronic administration of E2 both before and immediately after CCI conferred neuroprotection, reducing neurological severity score, brain infarction, and edema in TBI mice. Additionally, E2 improved many aspects of deleterious effects of TBI on the hippocampus, including neuronal apoptosis, dysfunction in spatial memory, reduction in NR2B, enhancement of oxidative stress, and activation of ERK1/2 pathway. The present study provides clue for the notion that E2 has therapeutic potential for both prevention and intervention of TBI‐induced brain damages. Abstract : Chronic administration of E2 is neuroprotective in TBI model. ERK signaling pathway is involved in the neuroprotection of E2.